2006
DOI: 10.1007/s00542-006-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the demolding forces during hot embossing

Abstract: Hot embossing is one of the main processing techniques for polymer microfabrication, which helps the LIGA (UV-LIGA) technology to achieve low cost mass production. When hot embossing of high aspect ratio microstructures, the deformation of microstructures usually occurs due to the demolding forces between the sidewall of mold inserts and the thermoplastic (PMMA). The study of the demolding process plays a key role in commercial manufacturing of polymer replicas. In this paper, the demolding behavior was analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 4 publications
2
41
0
1
Order By: Relevance
“…They reported that the farther the features are from the shrinking center, the harder the demolding becomes. This is in accordance with FEM calculations for the hot embossing process conducted by Guo et al (2007), who concluded that the thermal stress is a function of the orientation of the micro-structures relative to the shrinkage direction [5]. In practice, the orientations of structures and stress barrier should be kept coincident with the shrinkage center, e.g.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…They reported that the farther the features are from the shrinking center, the harder the demolding becomes. This is in accordance with FEM calculations for the hot embossing process conducted by Guo et al (2007), who concluded that the thermal stress is a function of the orientation of the micro-structures relative to the shrinkage direction [5]. In practice, the orientations of structures and stress barrier should be kept coincident with the shrinkage center, e.g.…”
Section: Introductionsupporting
confidence: 88%
“…This behavior was attributed to the introduction of thermal stresses into the PMMA, which caused part failure. The investigation on the design of the micro-structures confirmed favorable placement close to the gate and in flow direction in accordance to Heckele and Schomburg (2004) [4] and Guo et al (2007) [5], although the influence was minor due to the low impact of shrinkage on the demolding energy (compare Figure 3). PP displays the lowest overall demolding energies, due to its high elasticity and low tendency for surface adhesion to the stamper.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…또한 측벽의 표면 거칠기에 따라 이형력에 차이가 있음이 연구되었다 [2] . Yuhua Guo [3,4] 은 ABAQUS/Standard을 사용하여 Hot embossing 공정에서 금형과 polymer의 수축차이로 인한 열응력에 대하여 연 . .…”
Section: 서 론unclassified
“…In addition the use of Ni-PTFE as a mould material was recommended to achieve lower surface energy and friction force. Simulated results were presented by Guo et al [24].…”
Section: Embossingmentioning
confidence: 99%